Privatisasi Sempadan Pantai oleh Akomodasi Pariwisata di Denpasar - Alzaena Geanina Irnawan; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2019)
The privatization of the current coastal border began to bloom in many areas of Bali. No exception in Sanur Beach, Denpasar. In this study the privatization of coastal border is done by the accommodation provider of Santrian Resorts and Villas, which houses two hotels, including Puri Santrian A Beach Resort and Spa and Griya Santrian A Beach Resort. The purpose of this research is to know the form of privatization conducted by Santrian Resorts and Villas at Sanur Beach. As well as knowing the Denpasar city government policy on the privatization of beach border in Sanur Beach. The research methodology used in this research is qualitative research. The method are use in-depth interview technique and observation. Santrian Resorts and Villas is right to practice the privatization of coastal border. Therefore, many activities of tourists, tourists and informal business actors in the field of tourism becomes disrupted. Although there is already a policy on coastal border made by the Denpasar City Government, the policy is considered not yet firm in following up the violation. This is one reason why the practice of beach border privatization is still rife. Keyword : Tourism Policy, Privatization of Coastal Border, Tourism Law